2023
DOI: 10.3390/foods12051002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Changes on the Natural Prevalence of Fusarium Mycotoxins in Maize Harvested in Serbia and Croatia

Abstract: Ongoing climate change may affect the susceptibility of plants to attacks by pathogenic, mostly mycotoxigenic fungi with a consequent increase in the presence of mycotoxins. Fusarium fungi represent one of the most important producers of mycotoxins, and are also important pathogens of agricultural crops. Therefore, the main aim of the study was to estimate the impact of weather parameters on the natural occurrence of Fusarium mycotoxins, such as deoxynivalenol (DON), fumonisins B1 and B2 (FUMs), zearalenone (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Maize grains can be infected with various species of Fusarium fungi, such as F. graminearum , F. culmorum , F. langsethiae , F. poae , F. equiseti , F. sporotrichioides , and F. verticillioides [ 18 , 19 ]. The studies conducted in Poland confirmed that F. verticillioides , F. culmorum , F. graminearum , F. sporotrichioides , and F. poae are among the most common Fusarium species in maize [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Maize grains can be infected with various species of Fusarium fungi, such as F. graminearum , F. culmorum , F. langsethiae , F. poae , F. equiseti , F. sporotrichioides , and F. verticillioides [ 18 , 19 ]. The studies conducted in Poland confirmed that F. verticillioides , F. culmorum , F. graminearum , F. sporotrichioides , and F. poae are among the most common Fusarium species in maize [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Each treatment was replicated in four blocks (twenty-four blocks in total). To control weeds, maize was sprayed with herbicide ESTET ® 600 EC (active substance 2.4 D acid 600 g L −1 ) 0.6 L ha −1 one month after the seeding and repeatedly after two weeks with Nicogan ® (active substance nicosulfuron 40g L −1 ) 0.75 L ha −1 (BBCH [13][14][15][16][17][18][19]. No other plant protection products were used.…”
Section: Field Trial Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…When analyzing the ten-year results from 2012 to 2022, the highest levels of DON and ZEN were found in maize samples from 2014. This could be due to the extreme rainfall observed in both countries in that year [ 7 ].…”
Section: Introductionmentioning
confidence: 99%